SISTEM INFORMASI DESA SEBAGAI UPAYA PENINGKATAN LAYANAN DI KANTOR DESA ROPANG BERBASIS WEB - Adrian Julian Pratama; Rodianto (Universitas Teknologi Sumbawa, 2023)
Information System is an accurate presentation of the state or activity of the organization. Information is relevant if it can support decision making because it provides additional knowledge or value to decision makers, especially in government/village officials. The method used in designing Web-Based Information Systems is to use the Waterfall method, which is a classical model that is systematic, sequential in building software which has five stages, namely Requirements definition, System and software design, Implementation and unit testing, Verification and system testing, and Operation and maintenance . The information system as an effort to improve services at the WEB-BASED ROPANG village office has been successfully created using the PHP (Hypertext Prepocesor) programming language with the CodeIgniter framework and MySQL database so that the existence of a service improvement information system helps facilitate the work of computer operators in ROPANG village in providing services, the community also can do online management.